Letting the World Happen - Keathley, Christian (2014)
Laura Mulvey’s Death 24x a Second and my own Cinephilia and History, or The Wind in the Trees, which appeared in print within a few months of one another, share a similar set of concerns: the power of the filmic detail, that detail’s relation to film history and history in general, and the ways in which new digital technologies (with random access, freeze frame, and slow motion) encourages a spectatorial posture — one we generally associate with the cinephile — that facilitates the discovery of such moments.  Mulvey identifies two types of cinephile spectator — the pensive and the possessive — and notes that, in spite of their apparent differences, the intellectual curiosity of the first and the fetishistic fascination of the second are inevitably intertwined.  A discussion of several moments from Frank Capra’s It Happened One Night (1934) demonstrates this happy entanglement.